Tingkat Partisipasi Pendonor Reaktif IMLTD terhadap Konseling Pascadonor - Sitti Rahbiah Akram; Ririn Feriana Basri; Dahniar, Dahniar; A. Arviani Desianti Nur (Yayasan Literasi Sains Indonesia, 2025)
Screening for Transfusion-Transmissible Infections (TTIs) is an essential process in obtaining safe blood. Donors with reactive screening results must receive counseling, which is preceded by a notification process informing the donor of their test results, followed by post-donation counseling. Post-donation counseling is crucial to gather demographic information and assess risk exposure among donors with positive results. This study aims to determine the level of participation of reactive donors in attending post-donation counseling. It is a quantitative descriptive study using secondary data from the Blood Transfusion Unit of the Indonesian Red Cross (UTD PMI) of South Sulawesi Province. The study population consisted of donors who tested reactive for Transfusion-Transmissible Infections, with samples being those reactive donors who attended post-donation counseling. The results showed that out of a total of 353 reactive donors, only 33% attended counseling, while 67% did not. Several factors contributed to the absence of reactive donors during counseling sessions, including difficulties in contacting the donors and a lack of willingness to attend counseling. Considering the importance of donor counseling for the donors themselves, their families, and the community, it is a crucial activity to implement. Donor counseling contributes to the continuity of health services, plays a key role in preventing further transmission of infections, assists in outbreak control, and helps reduce the disease burden on the national health system.